Alkylation of Xylenes with Cyclohexene in the Presence of p-Toluenesulphonic Acid - Saha, Manoranjan; Dey, Haradhan Chandra; Karim, Mohammad Ziaul; Ismail, Mohammad; Saha, Dipti (Bangladesh Journal of Scientific and Industrial Research, 2008)
Isomeric xylenes have been cycloalkylated with cyclohexene in the presence of p-toluenesulphonic acid as catalyst. The effects of the variation of temperature, molar ratio of xylene to cyclohexene, time of reaction and amount of p-toluenesulphonic acid on the reactions have been studied and cyclohexyl xylenes have been obtained in high yield.